La question énergétique au cœur du développement durable au Maroc : Liens entre développement économique, consommation d’énergie, émissions de Gaz à effet de serre et climats - Bikrat Fatiha; Karim Mohamed (African Scientific Journal, 2022)
This paper focuses on the environment issue that is related to the question of energy and its economic impact. It presents the relevant environmental implications of both energy consumption and economic growth in a global and a national context, and also gives an overview of the important policies and environmental initiatives adopted. Concerning the empiric study, it consists in the examination of the relationship between energy, environment and economy in the framework of the Kaya identity, which is designed to estimate the CO2 emissions depending on other factors such as the energy intensity, the index of energy soiling, the population and the gross domestic product per capita.